Dietary combination of chelated zinc and threonine and effects on egg production, egg quality and nutrient balance of Brown laying hens from 20 to 49 weeks of age - Neto, M.A. Trindade; Dadalt, J. C.; Tse, M. L.P. [UNESP] (Elsevier, 2020)
Studies have evaluated the effects of zinc (Zn) supplementation as an important dietary factor that regulates intestinal amino acid metabolism, protecting and preventing diarrhea. Threonine (Thr) also plays an important role in intestinal mucosa, playing a key role in the innate immune defence of mucosa. Thus, the present study evaluated the combined effects of Thr and chelated Zn on egg production and egg quality of brown laying hens from 20 to 48 weeks and on nutrient balance at week 49. The hypothesis was that a lower level of Zn chelated in the diet could be favorable for the use of Thr by laying hens. Thus, two experimental designs were made. Experiment number 1: A completed randomized design with six replicate cages per treatment was done. The structure of the treatment was a 4 × 5 factorial arrangement with five levels of total Thr (6.14, 6.98, 8.75, 10.06 and 10.55 g/kg) and four analyzed levels of Zn (31, 73, 104 and 121 mg / kg). A total of 120 cages was used. Each cage had eight hens. In this experiment the experimental unit was the cage with 8 hens. The response variables analyzed were related to egg production and quality. Experiment number 2: It was identical to experiment 1, but only four repetitions were used per treatment and each cage had 4 hens. The experimental unit was the cage with 4 hens. The response variables analyzed were related to the nutrient balance, and apparent metabolizable energy corrected by nitrogen (AMEN). An interaction effect between Zn and Thr levels was observed on egg production, egg weight, nitrogen balance and AMEN. Quadratic equations indicated that increasing dietary levels of Zn reduced Thr estimates for hens. General performance results suggest a total Thr concentration of 8.38 ± 0.43 g/kg or 880 ± 43 mg/day, however, a level of chelated Zn above 40 mg/kg negatively affected egg quality. Corn and soybean meal diet naturally provided the zinc requirement egg production. Higher Zn levels can reduce nutrient and energy intake and efficiency, limiting its retention by laying hens and affecting productive performance. As for interaction, the apparent lower estimate of Thr to ensure egg production and egg weight with increased Zn concentration in the diet may imply a gradual increase in Zn excretion. Thus, costs related to food and the environment must also be considered.
Keywords: chelated zinc; egg production; egg quality; laying hens; nutrient balance